Social Considerations For Women's Participation - Sh. Teshaboyeva (The American Journal of Social Science and Education Innovations, 2021)
The article examines the issues of protecting the rights and interests of women, creating decent working and living conditions for them, the rule of law in realizing their abilities and potential.